2023
DOI: 10.1371/journal.pone.0284445
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapist beliefs and perspectives on virtual reality supported rehabilitation for the management of musculoskeletal shoulder pain: A focus group study

Abstract: Background Virtual Reality (VR) is an immersive computer-generated environment that provides a multi-sensory experience for the user. Modern technology allows the user to explore and interact with the virtual environment, offering opportunities for rehabilitation. The use of immersive VR in the management of musculoskeletal shoulder pain is relatively new and research is required to demonstrate its feasibility and effectiveness in this field. Aim The aims of this study were, firstly, to explore physiotherapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…The rehabilitants as well as the therapists suggested that VR offered an enjoyable way to exercise and that this could motivate people to engage in rehabilitation programs. These experiences appear to reflect those described by Brady et al [53], who pointed out, as a result of focus groups with physiotherapists, how most participants smiled when they described their experience of using VR, because it is fun. For neurological rehabilitation that often involves extensive repetition of basic tasks, VR has been shown to provide an engaging platform for rehabilitation by making therapy more stimulating [54,55].…”
Section: Discussionsupporting
confidence: 81%
“…The rehabilitants as well as the therapists suggested that VR offered an enjoyable way to exercise and that this could motivate people to engage in rehabilitation programs. These experiences appear to reflect those described by Brady et al [53], who pointed out, as a result of focus groups with physiotherapists, how most participants smiled when they described their experience of using VR, because it is fun. For neurological rehabilitation that often involves extensive repetition of basic tasks, VR has been shown to provide an engaging platform for rehabilitation by making therapy more stimulating [54,55].…”
Section: Discussionsupporting
confidence: 81%
“…Comparatively, some prior studies have reported challenges in recruiting and retaining participants in VR interventions, often citing concerns related to technology complexity, discomfort, or motion sickness (Brady et al, 2023;Chang et al, 2020;Weech et al, 2019). The exceptionally positive recruitment and retention rates observed in this study suggest that, with careful design and implementation, VR can be wellreceived and embraced by nursing students.…”
Section: Discussionmentioning
confidence: 70%
“…This is in line with a previous study that found that eHealth use was associated with physiotherapy practice size [ 33 ], possibly due to more financial resources. In contrast to this potential facilitator, implementation of VR in healthcare might be hindered due to technical limitations of the device, lack of comparative research and perceived increased work pressure [ 35 – 37 ]. Some of these barriers were mentioned by the physiotherapists in this survey, but the main reason for surveyed physiotherapists not using therapeutic VR was that they were unfamiliar with using therapeutic VR.…”
Section: Discussionmentioning
confidence: 99%